2023
DOI: 10.1002/pc.27281
|View full text |Cite
|
Sign up to set email alerts
|

Effect of silicon dioxide and organized montmorillonite on the crystalline morphology and dielectric properties of polypropylene‐based composites

Abstract: Polypropylene (PP), a thermoplastic material that can be recycled by melting, is viewed as a potential alternative to cross-linked polyethylene for insulation.In this work, PP-based composites were fabricated with surface-modified silicon dioxide (SiO 2 ), organized montmorillonite (OMMT), and polyolefin elastomer (POE) as fillers via a two-step melt blending method. The dispersion states of SiO 2 nanoparticles, OMMT, and POE in PP and their effects on PP crystallization were investigated. Moreover, the elonga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
(45 reference statements)
0
11
0
Order By: Relevance
“…They showed that graphene allowed the degree of crystallinity to decrease and the level of electrical conductivity to increase. In addition, Gao et al 37 found that homogeneously dispersed silicon dioxide and montmorillonite in PP/POEs blends acted as heterogeneous nucleation sites, enhancing the samples' volume resistance, dielectric properties, and mechanical strength with changing degree of nucleation.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that graphene allowed the degree of crystallinity to decrease and the level of electrical conductivity to increase. In addition, Gao et al 37 found that homogeneously dispersed silicon dioxide and montmorillonite in PP/POEs blends acted as heterogeneous nucleation sites, enhancing the samples' volume resistance, dielectric properties, and mechanical strength with changing degree of nucleation.…”
Section: Introductionmentioning
confidence: 99%
“…However, they reported formulations with up to 50% recycled material exhibited potential for electric insulating systems. In addition to the limited research available on the dielectric properties of recycled polymers, it is worth noting that several studies and review articles have examined the dielectric properties of virgin materials 12–15 . These studies provide valuable insights into understanding the behavior of dielectric properties of recycled materials.…”
Section: Introductionmentioning
confidence: 99%
“…For example, styrene ethylene butylene styrene (SEBS), styrenic block copolymers (SBS), ethylene vinyl acetate copolymer (EVA), polyolefin elastomer (POE) and other elastomers blended with PP materials to improve the matrix toughness has also been widely proven. [9][10][11][12] Among them, POE materials have excellent electrical properties, processing properties, and heat and cold resistance properties, which are favored by scholars. 13,14 As a semi-crystalline thermoplastic material with high crystallinity, the crystallization behavior of polypropylene has a close correlation with the macroscopic force-electric properties of the material, and changing the crystallization behavior of polypropylene is bound to have an obvious effect on the properties of polypropylene.…”
Section: Introductionmentioning
confidence: 99%
“…To address such problems, the industry usually uses the addition of elastomers to form blends with polypropylene to improve the PP and elastomers have been widely studied. For example, styrene ethylene butylene styrene (SEBS), styrenic block copolymers (SBS), ethylene vinyl acetate copolymer (EVA), polyolefin elastomer (POE) and other elastomers blended with PP materials to improve the matrix toughness has also been widely proven 9–12 . Among them, POE materials have excellent electrical properties, processing properties, and heat and cold resistance properties, which are favored by scholars 13,14 …”
Section: Introductionmentioning
confidence: 99%